Analysis of Basic Principles of Education Providers and Scientific Trees in Science Literacy-Based Learning in Elementary Schools: A Multi-Aspect Review - Jazilah Nailatun Ni’mah; Budi Purwoko; Wahono Widodo (PT. Pusmedia Group Indonesia, 2026)
Science literacy-based learning in primary schools plays a strategic role in developing critical thinking, problem-solving, and evidence-based decision-making skills as important competencies of the 21st century. However, the implementation of learning in the field is still dominated by the orientation of material mastery and the achievement of cognitive learning outcomes, so that the development of science process skills and students' scientific disposition has not been carried out optimally. This study aims to analyze the implementation of basic principles of education and science trees in science literacy-based learning through a multi-aspect review that includes philosophical, sociological, anthropological, psychological foundations, as well as ontological and epistemological perspectives. This study uses a descriptive qualitative approach carried out at SDN Plumbon 2 with teachers and 20 fourth grade students as research subjects. Data was collected through observation, interviews, and documentation, then analyzed using the stages of data reduction, data presentation, and conclusion drawing with validity tests through source triangulation and triangulation techniques. The results of the study show that science literacy learning has accommodated several basic principles of education through the association of materials with daily life and the application of discussion activities. However, learning is still dominated by a teacher-centered, concept-mastery-oriented approach, and uses success indicators that emphasize cognitive aspects rather than process skills and scientific disposition. Furthermore, the application of the science tree concept has not shown complete integration between the foundation of education, the learning process, and the results of science literacy. The contribution of this research lies in the development of an integrative analytical framework that connects basic education principles, ontological and epistemological dimensions, and the concept of the science tree as a basis for evaluating the success of science literacy learning more comprehensively. The framework expands the learning evaluation approach, which previously focused on cognitive outcomes, to an assessment that includes the process of knowledge formation and the students' scientific disposition.